Using New Media and Social Media in Disaster Communication - Dhyah Ayu Retno Widyastuti (Komunikator, 2021)
New media and social media have changed the frame of communication that appears quickly, is interactive, and has no geographical boundaries. The media plays an essential role in disseminating accurate and responsible information in a disaster situation. The strategy of using communication media will reduce the impacts arising from disasters in the mitigation, preparedness, response, and recovery phases. Through a literature review, the author presents disaster communication, strategies, and using media in disasters. The research use case studies are the natural disaster of Mount Merapi and the Covid-19 pandemic to represent non-natural disasters. The results of the analysis show that sensitivity to the situation is an adequate response in a disaster. Furthermore, new media and social media tend to be sufficient as the primary source of information for the public, coordination, and fundraising. The effectiveness of media use in the Merapi disaster is the beginning of new media and social media in disaster communication in Indonesia. This media is also used in disaster management during the COVID-19 pandemic. The use of media in both case studies is considered adequate to reduce the negative impacts arising from the disaster. It is hoped this idea will contribute to disaster communication studies.